A Cognitive Positive Discourse Analysis of English Motivational Speeches - Kawa Abdulkareem Sherwani (International Journal of Advanced Science and Technology, 2020)
In the last thirty years a lot of studies have been conducted using critical discourse analysis. The greater part of these researches focus on and criticize the negative role of dominant discourse on social inequality and discrimination. Unlike these researches, this study tries to explore another aspect of discourse which is the role of positive attitudes in motivational speeches on the peoples’ behaviors and cognitions. In this study the positive discourse analysis, a counterpart of critical discourse analysis, is taken as an approach to analyze the data. The data is taken from American motivational speeches by famous speakers. Since the paper deals with the role of positive thinking in relation to discourse and cognition, the approach is a combination between positive discourse and cognitive analysis; therefore, it is called cognitive positive discourse analysis. This study concentrates on progressive discourse rather than oppressive one. Three analytical tools of discourse analysis are used to analyze the data, including: narrative, hyperbole and framing. The study attempts to answer a number of questions connected to the effect of discourse on human action. It points out that attitude cannot be dealt with without considering beliefs, goals and behaviors. These aspects are not static; the positive discourse can affect the human cognition and change the attitudes, beliefs, intentions, goals and behaviors.